2020
DOI: 10.3390/app10020708
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study for the Effects of Temperature Dependent Viscosity Flow of Non-Newtonian Fluid with Double Stratification

Abstract: The main aim of the current study is to determine the effects of the temperature dependent viscosity and thermal conductivity on magnetohydrodynamics (MHD) flow of a non-Newtonian fluid over a nonlinear stretching sheet. The viscosity of the fluid depends on stratifications. Moreover, Powell–Eyring fluid is electrically conducted subject to a non-uniform applied magnetic field. Assume a small magnetic reynolds number and boundary layer approximation are applied in the mathematical formulation. Zero nano-partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Waqas 4 reported the flow, heat transfer characteristics of the ferromagnetic stretching flow of Williamson fluid subject to homogeneous and heterogeneous chemical reactions. A numerical investigation is made to study the influence of nonuniform viscosity and double stratification on the motion of Powell-Eyring fluid over nonlinear stretchable sheet by Wahab et al 5 Xiong et al 6 discussed and reported on the multiple solutions of a Cross nanofluid via a thin vertical needlepoint under influence of Darcy-Forchheimer. Across stretching surface, the heat transfer characteristics for an MHD stagnation point flow of Cross fluid are reported on by Ijaz Khan et al 7 Consideration of bioconvective flow of MHD Cross nanofluid along with gyrotactic microorganisms and activation energy is another report by Shi et al 8 Muhammad et al 9 investigated the numerical results for a bioconvective flow of Cross nanofluid with swimming microorganisms across a cylinder under thermal conductivity and melting process.…”
Section: Introductionmentioning
confidence: 99%
“…Waqas 4 reported the flow, heat transfer characteristics of the ferromagnetic stretching flow of Williamson fluid subject to homogeneous and heterogeneous chemical reactions. A numerical investigation is made to study the influence of nonuniform viscosity and double stratification on the motion of Powell-Eyring fluid over nonlinear stretchable sheet by Wahab et al 5 Xiong et al 6 discussed and reported on the multiple solutions of a Cross nanofluid via a thin vertical needlepoint under influence of Darcy-Forchheimer. Across stretching surface, the heat transfer characteristics for an MHD stagnation point flow of Cross fluid are reported on by Ijaz Khan et al 7 Consideration of bioconvective flow of MHD Cross nanofluid along with gyrotactic microorganisms and activation energy is another report by Shi et al 8 Muhammad et al 9 investigated the numerical results for a bioconvective flow of Cross nanofluid with swimming microorganisms across a cylinder under thermal conductivity and melting process.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded in their study that the Casson fluid model shows a good heat transport analysis compared to the Newtonian model. Wahab et al 14 elucidate the impact of viscosity, which depends on temperature, on non-Newtonian fluid flow together with double stratification. Their flow equations were solved numerically and a decrease in velocity profile is observed with large stratification parameter.…”
Section: Introductionmentioning
confidence: 99%
“…They found out that a large Prandtl number brings a degeneration to thermal boundary layer thickness. Wahab Hafiz et al 16 have done an examination on the influence of viscosity which is a function of temperature as non-Newtonian liquid motion with double stratification numerically. Venkateswarlu and Satya Narayana 4 elucidated the impact of varying thermal conductivity on the Casson fluid motion of MHD using the shooting method.…”
Section: Introductionmentioning
confidence: 99%